CLINICAL POSSIBILITIES FOR THE ASSESSMENT OF PAIN IN DENTISTRY AND OUTPATIENT ORAL SURGERY- GENERAL ASPECTS - Oana Elena Ciurcanu; Monica Mihaela Scutariu; Octav Mihai Boaru; Claudiu Topoliceanu; Doriana Agop-Forna (Romanian Society of Oral Rehabilitation, 2019)
The uncontrolled negative emotional stress, will increase the intensity of the pain experience due to the decrease of the pain threshold and to changes of the tolerance to medication. The most dental treatments are performed under various types of anaesthesia (loco-regional, potentialised, general). In some clinical situations and for specific dental procedures (especially oral surgery) the dentists use a combination of psychologic preparation, pharmaco-therapeutic sedation and loco-regional anaesthesia. The pre-anaesthesia and pre-medication have the role to control the psychic reaction to pain. For the most patients with a balanced psychic, calm and cooperative, the loco-regional anaesthesia techniques can be used successfully